Debit card adoption: a case study of Bank Rakyat / Norhayati Baharun ... [et al.] - Baharun, Norhayati; Md Radzi, Rahah; Mat Radzi, Siti Hajar; Hamzah, Mohd Faizal (2017)
The evolution of payment system in Malaysia has shifted from cash to cashless or paperless in alignment of globalization and digital era particularly in the banking system. The technology advancement enormously improves the efficiency of payment system that led to the recognition of debit card usage for public convenience. Debit card provides a great deal of convenience and security in managing bank savings account in terms of cashless transactions when making any payment. For this reason, a case study was conducted which focused on the adoption of debit card among the customers of Bank Kerjasama Rakyat Malaysia Berhad (BKRMB) also known as Bank Rakyat. As evident in the literature review obtained from previous studies, the adoption of debit card was significantly associated with the customers' demographic background, customers' perceptions, and technological factors. Hence, an investigation has been done in this study which based on the customers' perceptions aimed at determining the impact of these three factors towards the adoption of Bank Rakyat debit card. A survey method was adopted which involved three hundred respondents selected via the convenience sampling technique. Findings revealed that technological factors and customers' perceptions significantly played an important role in the adoption of Bank Rakyat debit card. Therefore, this possibly provides a better input for the Bank Rakyat in strategizing their marketing plans or procedures for future development on its debit card.